PEMANFAATAN TEPUNG KENTANG SEBAGAI MASKER UNTUK PERAWATAN KULIT WAJAH BEKAS JERAWAT - Fransisca, Devi Dwi; Hayatunnufus, Hayatunnufus; Rosalina, Linda (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This is a quasi experiment method with non equivalent control group design. Theobject of this research is skin-face with acne’s marks of State University of Padang within 17-25 years old, with the same criteria. The sample was taken by purposive sampling teaching with volunteers . The data were analyzed by descriptive and ANAVA . the result showed that skin face treatment 1x3 days with pop ato mask significant change. For better than 1x7 days. With skin indicaturs, skin brightness and acne’s mask. with significant result 0,000< 0,050 that the hypothesis is receired. According by the hypothesis is received. According by the DUNCAN test, showed more efficient and effective.Keywords :Potato Flour Mask, Skin Face With Acne’s Marks